2012
DOI: 10.2196/resprot.2205
|View full text |Cite
|
Sign up to set email alerts
|

Development of Smartphone Applications for Nutrition and Physical Activity Behavior Change

Abstract: BackgroundYoung adults (aged 18 to 35) are a population group at high risk for weight gain, yet we know little about how to intervene in this group. Easy access to treatment and support with self-monitoring of their behaviors may be important. Smartphones are gaining in popularity with this population group and software applications (“apps”) used on these mobile devices are a novel technology that can be used to deliver brief health behavior change interventions directly to individuals en masse, with potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 34 publications
3
112
0
5
Order By: Relevance
“…Figure 2 trial or outcome studies, five articles focused on software design and evaluation and the remaining articles are on focus groups and interview studies on stakeholders' opinions on smart phone apps for physical activity (see Table 1). [25] × × [26] × [27] × × × × × × × × × [28] × × × × × × × × [29] × × × × [30] × × × [31] × [32] × × × × × × × × × × × × [33] × × [34] × × × × × × × [35] × × × × [36] × × × × × × [37] × [38] × × × [39] × × × × × [40] × [41] × [42] × × × × [43] × × [44] Illustrations in figure 2 and table 2 show features that are highly present in articles on physical activity intervention studies, those features that were occasionally mentioned, or those that were not cited often in these articles. Visualisation of persuasive features is presented to provide more insights about the highlights, 9 gaps and blank spots [45] in current mobile application persuasive design features on physical activity.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 trial or outcome studies, five articles focused on software design and evaluation and the remaining articles are on focus groups and interview studies on stakeholders' opinions on smart phone apps for physical activity (see Table 1). [25] × × [26] × [27] × × × × × × × × × [28] × × × × × × × × [29] × × × × [30] × × × [31] × [32] × × × × × × × × × × × × [33] × × [34] × × × × × × × [35] × × × × [36] × × × × × × [37] × [38] × × × [39] × × × × × [40] × [41] × [42] × × × × [43] × × [44] Illustrations in figure 2 and table 2 show features that are highly present in articles on physical activity intervention studies, those features that were occasionally mentioned, or those that were not cited often in these articles. Visualisation of persuasive features is presented to provide more insights about the highlights, 9 gaps and blank spots [45] in current mobile application persuasive design features on physical activity.…”
Section: Data Extractionmentioning
confidence: 99%
“…Suggestion also came in the form of motivational text suggestions [39] or video clips that provided tips or motivational messages to the user [40]. A study of the attitudes of users towards the persuasive features revealed that users may sometimes perceive suggestions to be too obtrusive to them [28].…”
Section: Dialogue Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of smartphone and tablet applications (apps) has turned these devices into multifunctional tools. They can be used to amalgamate data collected from sensors, the Internet, and, most importantly, online social networks and can therefore function as interventional tools to treat and prevent obesity [7]. Smartphones and tablets have been used to raise awareness in different health-related areas, such as smoking and sexual health [8].…”
Section: Introductionmentioning
confidence: 99%
“…This particular problem was experienced by researchers who developed a physical activity and nutrition web-based application; they found that the slow operating speed was a barrier to their participants' engagement. 16 The application development process is a complex network of interwoven considerations, all with long-term ramifications, and many health professionals will not have the technical experience to navigate the options. 17 Indeed, keeping up to date with the progression of technology is something that has been identified as a challenge by public health researchers.…”
Section: Introductionmentioning
confidence: 99%